In utero nanoparticle delivery for site-specific genome editing - Adele S. Ricciardi; Raman Bahal; James S. Farrelly; Elias Quijano; Anthony H. Bianchi; Valerie L. Luks; Rachael Putman; Francesc López-Giráldez; Süleyman Coşkun; Eric Song; Yanfeng Liu; Wei-Che Hsieh; et al. (Nature Communications, 2018)
The correction of genetic defects in utero could allow for improved outcomes of gene therapy. Here, the authors demonstrate safe delivery of nanoparticles to fetal mouse tissues, and show that nanoparticles containing peptide nucleic acids to edit the beta-globin gene are effective in a mouse model of beta-thalassemia.